Sinkretisasi Siwa-Buddha di Pura Yeh Gangga Desa Perean Tengah Kecamatan Baturiti Kabupaten Tabanan - Kadek Anggi Dwi Yanti (Kamaya: Jurnal Ilmu Agama, 2022)
This research was conducted based on the author's interest in harmony in Bali. Harmony between religious communities in the middle of the island of Bali, is not only influenced by national conventions on politics and social, but also because of local wisdom about syncretization in religious aspects. The teachings of Shiva, which dominate and are recognized as the main stream and even animate most Hindus in Bali, do not forget to also accommodate and harmonize themselves in other teachings, one of which is Buddhism. from this, the existence of Buddhism is still growing today. One of the reflections on the unification of the values ​​of Shiva-Buddhist teachings can be found in the Yeh Gangga Temple, Central Perean Village. This research is a descriptive qualitative field research. The primary data sources in this study were the Yeh Gangga Temple and Hindus and Buddhists as the worshipers. Data collection was carried out using the snow ball technique. The results of this study have occurred Syncretization of Shiva-Buddhist Teachings at Yeh Gangga Temple including (1) the history of the unification of Shiva-Buddha, (2) the arrival of Shiva-Buddha in Perean Tengah Village, (3) The Syncretization Process of Shiva-Buddhist Teachings, and (4) Meru Tumpang Pitu as a form of syncretization. The driving factors for syncretization include (1) Religious System Factors, (2) Social Factors. The implications of the syncretization of Shiva-Buddhist teachings at Yeh Gangga Temple include (1) Social implications and (2) Theological implications.